Empowering health decisions - Greenberg, Jerrold S. (Jones & Bartlett Learning, 2013)
Empowering Health Decisions offers a personal health text focused on essential content for students to assist them in making informed decisions about their health. This text is unique from other personal texts on the market in that it focuses on decision-making models and theories of behavior change. These models are carried throughout each chapter and will describe how it can be used to make health enhancing decisions specific to the chapter content